1991
DOI: 10.1164/ajrccm/143.3.501
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Cohort Study of the Risk of Tuberculosis Among Women of Childbearing Age with HIV Infection in Zaire

Abstract: To determine the risk of active tuberculosis associated with HIV infection, we retrospectively studied a cohort of HIV-seropositive and HIV-seronegative women participating in an HIV perinatal transmission study in Kinshasa, Zaire. After a median follow-up of 32 months, new cases of proven pulmonary or clinically diagnosed tuberculosis occurred in 19 of the 249 HIV-seropositive women (7.6%, 3.1 cases per 100 person-years) compared with 1 of the 310 HIV-seronegative women (0.3%, 0.12 cases per 100 person-years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
2

Year Published

1992
1992
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(23 citation statements)
references
References 5 publications
2
19
0
2
Order By: Relevance
“…Denominou-se esse coeficiente de adoecimento de m 1 . Entre os já infectados (P.p) poderão sofrer reinfecções exógenas que dependerá do risco de infecção tuberculosa (r) existente na comunidade.…”
Section: Modelounclassified
“…Denominou-se esse coeficiente de adoecimento de m 1 . Entre os já infectados (P.p) poderão sofrer reinfecções exógenas que dependerá do risco de infecção tuberculosa (r) existente na comunidade.…”
Section: Modelounclassified
“…A study from Zaire showed that the risk of TB in HIV-positive mothers was three times more than that in HIV-negative mothers (2). Infants born to HIV-infected mothers are susceptible to both HIV infection and TB.…”
mentioning
confidence: 99%
“…Epidemiologic data suggest that active TB accelerates the natural progression of HIV infection. In a retrospective cohort study of HIV-infected women from Zaire, investigators estimated the relative risk of death to be 2.7 among women with active TB compared with those without TB [19] . In a retrospective cohort study of HIV-infected subjects from the United States, active TB was associated with an increased risk for opportunistic infections and death [15] .…”
Section: Tb and Hiv/aidsmentioning
confidence: 99%